ANALISIS MOTIVASI BELAJAR MAHASISWA PADA PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Singgih, Galih Ristu; Fitriani, Risma (Lentera: Jurnal Ilmiah Kependidikan, 2021)
In the implementation of online learning there are often several obstacles, it can affect student motivation in following the learning process. This study aims to explain the conditions of student motivation in participating in online learning during the Covid-19 pandemic. The study used a quantitative approach with a survey method. The study was conducted at Universitas Singaperbangsa Karawang involving 20 seventh semester student in Industrial Engineering study program. Data collection techniques in this study used survey techniques with a Likert scale. The data analysis technique used in this study was to calculating the percentage of each indicator data, then the data obtained from the percentage results are then analyzed in depth with the method of analysis. The results of this study indicate that the learning motivation of the 7th semester students of the Industrial Engineering study program at the Singaperbangsa Karawang University is classified as good, it is obtained from the acquisition of a motivation percentage score of 70%.